A Comparative Study on Pain Caused by Standard and Z-Track Method for I.M Injection - SH Mohamadzadeh; N Bahrani; N Mehrdad; S Jolaee (Tehran University of Medical Sciences, 2003)
Introduction: Pain caused by some therapeutic and nursing procedures has been a major concern of health care providers. Injection pain is a common complaint of patients. Materials and Methods: This quasi-experimental investigation was conducted to compare the pain intensity caused by standard, and Z-Track method for intramascullar (I.M) injection. The samples were 100 female nursing student volunteers that were selected by convenience sampling. Each sample was injected two times blindly: first by standard and then by Z-Track method, with 24 hours interval. None of them knew the method of injection for each time. The injection solution was 1 ml sodium chloride. Pain intensity was measured by a numerical pain assessment scale and pain experienced by every body was compared with herself. Results: The results showed that the pain associated with IM injection was significantly decreased when Z-Track method was used. Conclusion: The researcher can join to other authors stating that Z-Track can be the technique of choice for all I.M injections.